1999
DOI: 10.1111/jon19999272
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy (1H MRS) in Patients with Sporadic Cerebellar Degeneration

Abstract: The authors studied 23 patients with cerebellar degeneration including multiple systemic atrophy (MSA) and cerebellar cortical atrophy (CCA) by proton magnetic resonance spectroscopy (1H-MRS). 1H-MRS allowed noninvasive measurement of the signal intensities derived from N-acetylaspartate (NAA), creatine + phosphocreatine (CRE), and choline-containing compounds (CHO). There was significant reduction of the NAA/CRE level in the frontal cortex, putamen, cerebellar hemisphere and cerebellar vermis of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
4
3
0
Order By: Relevance
“…However, the location of their voxel in the dentate and peridentate region may not be representative of NAA/Cr loss, since the dentate nucleus is spared in SCA2. In accordance with a previous study that reported a significant correlation between the NAA/Cr level and the severity of clinical signs (26), the association between findings from MR volumetry/spectroscopy and cerebellar disability scores detected in the present study argues in favor of NAA as a valid noninvasive in vivo biomarker for neuronal dysfunction and/or atrophy in SCA2 and MSA‐C.…”
Section: Discussionsupporting
confidence: 93%
“…However, the location of their voxel in the dentate and peridentate region may not be representative of NAA/Cr loss, since the dentate nucleus is spared in SCA2. In accordance with a previous study that reported a significant correlation between the NAA/Cr level and the severity of clinical signs (26), the association between findings from MR volumetry/spectroscopy and cerebellar disability scores detected in the present study argues in favor of NAA as a valid noninvasive in vivo biomarker for neuronal dysfunction and/or atrophy in SCA2 and MSA‐C.…”
Section: Discussionsupporting
confidence: 93%
“…Low cerebellar and pontine NAA levels and NAA/Cr ratios in SCA2 and MSA-C relative to controls were reported previously [9, 11, 28] and indicate neuronal dysfunction/loss in these brain regions [29]. In addition to this well-established biomarker, we detected differences in myo -inositol, tCr (both putative markers of gliosis [30, 31]), glutamate, glutamine (potentially reflecting disruptions in glutamatergic neurotransmission [21]), and glutathione and ascorbate (potentially indicating oxidative stress) in patients with SCA2 and MSA-C relative to controls (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…NAA can be more easily accessible than MI because the methyl group of NAA can be obtained by the 1 H‐MRS both using long TE and short TE. In addition, several authors have reported the usefulness of NAA/Cr and NAA for the evaluation of MSA pathology 5–8. However, the previous study about AD and MCI19 and our data supported the superior utility of MI/Cr ratio as a diagnostic tool in evaluating the severity of neurodegenerative disorders compared to NAA and NAA/Cr.…”
Section: Discussionsupporting
confidence: 57%
“…Both compounds can be observed by 1 H‐MRS, and hence may be considered biomarkers of neuronal integrity and gliosis. Although both NAA and MI are important from the pathological point of view in MSA,3, 4 there was limited information about the role of MI in MSA 5–8…”
mentioning
confidence: 99%